Scaling up sweetpotato-led interventions for nutrition and food security, Tigray region, Ethiopia. Project profile. - International Potato Center (International Potato Center, 2019)
Tigray is one of the regions in Ethiopia with the highest levels of maternal and child malnutrition and food insecurity. Grain-led approaches have failed to address these issues, with vitamin A deficiency rates remaining high. This intervention aims to tackle the problem by promoting greater dissemination of biofortified orange-fleshed sweetpotato.